Research Progress of Decommissioned Solid Rocket Motor Charge Emptying and Recycling Technology - Zhou Yaping, Lin Zhihui, Wang Maoyu, Dong Jun, Liu Tiansheng, Qiao Haitao (Hangkong bingqi)
As the service life of solid rocket engines comes to an end, their operational reliability and performance stability gradually decline. Effectively disposing of large numbers of retired solid rocket engines has become a critical issue. This paper systematically analyzes six promising deactivation technologies for solid rocket engines with engineering application potential: liquid nitrogen cutting, cryogenic cycling, mechanical cutting, ignition testing, high-pressure jetting, and hydrodynamic cavitation. Firstly, the principles of these technologies and their application status in the disposal of retired engines are reviewed, with particular emphasis on their advantages in propellant removal and improving recovery efficiency. Comparative analysis reveals that high-pressure jetting and hydrodynamic cavitation technologies significantly outperform others in removing residual propellants, while also demonstrating higher safety levels. Furthermore, the recovered engine casings and composite propellants exhibit considerable potential for reuse. Engine casings can be repurposed for the manufacturing of new rocket components and propulsion systems, while propellants can be further developed for other chemical applications or waste heat recovery. Based on these findings, this paper proposes technical development suggestions for the resource utilization of large-caliber solid rocket engines, emphasizing the feasibility of integrating multiple deactivation technologies. This offers new insights and technical pathways for the resource recovery and reuse of military equipment.